Pelatihan Penulisan Karya Ilmiah dan Tata Cara Submit ke Jurnal Nasional Terakreditasi - Achmad Wicaksono; Achmadi Susilo; Rufi’i Rufi’i; Ristani Widya Inti (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Nowadays, the demands in education to publish scientific papers are increasing. However, some students still do not understand how to publish scientific papers in accredited national journals. This community service activity was carried out to equip final-year students to compile scientific papers that meet national standards. The method used in implementing this activity is the lecture and practice method. The presenter first explained the technique of writing scientific papers to the participants, then continued with the practice of submitting articles through the OJS facility. The community service results showed that most participants understood how to compile good and correct scientific papers. In addition, the participants who attended also seemed to understand the steps to submit articles through the OJS facility. Through this training, it is hoped that all final-year students can publish parts of their theses in accredited national journals.